MODEL PEMBELAJARAN BERDASAR MASALAH UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PADA PERKULIAHAN TEORI PELUANG - Sudi Prayitno (Jurnal Kependidikan, 2006)
Abstract The purpose of this research is to improve learning activity and achievement in Probability Theory, through the implementation of Problem-Based Learning (PBL). This research was done in three cycles on first semester students of Mathematics Education of the University Mataram, iin the academic year 2005/2006. In this research, the implementation of PBL model is combined with cooperative model in the phase of problem solving. By improving the quality of learning on each cycle, activity and achievement of students improved significantly, that is the average of achievement is 62.8 at the end of the first cycle, 71.6 in the second and 87.8 at the third. Students’ activity also improved, that is 47% in first cycle, 67% in second and 88% in third. It indicates that PBL implemented in the last cycle can be made as one of instruction model in university, especially for study of probability theory. Keywords: Problem-Based Learning (PBL), learning activity, learning achievement, and Probability Theory.